48.5k views
0 votes
5x + 6 = 2(2x - 3)
help

2 Answers

1 vote

Answer:

Not possible.

Explanation:

Start by doing the right side. Multiply 2 by 2x (4x) and 2 by -3 (-6).

Now you have 5x + 6 = 4x - 6.

Take away the 4x from right and take away 4x from 5x, giving you x alone.

Take away the 6 from the left, and take 6 away from the -6.

Now you’re at x = 0.

There isn’t a possible answer for this question.

User Sachi
by
5.1k points
2 votes
X=-12 that is the answer hope it helped:)
User Aidenhjj
by
5.1k points